2007
DOI: 10.1097/mpa.0b013e31802f0531
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Activates Rat Pancreatic Stellate Cells Through Protein Kinase C and p38 Mitogen-Activated Protein Kinase Pathway

Abstract: Our results indicate that high glucose concentrations stimulate PSC activation via PKC-p38 MAP kinase pathway and suggest that high glucose may aggravate pancreatic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 42 publications
2
30
0
2
Order By: Relevance
“…Previous studies have shown that PMA can induce p38 activation (Chang et al, 2005; Kitatani et al, 2006; Nomura et al, 2007) and implicated PKC upstream of p38 MAPK (Woo et al, 2005; Nomiyama et al, 2007). Given that PKC- δ and nSMase2 did not seem to interact, it became important to determine the role of PKC with respect to p38 MAPK in regulating nSMase2 translocation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that PMA can induce p38 activation (Chang et al, 2005; Kitatani et al, 2006; Nomura et al, 2007) and implicated PKC upstream of p38 MAPK (Woo et al, 2005; Nomiyama et al, 2007). Given that PKC- δ and nSMase2 did not seem to interact, it became important to determine the role of PKC with respect to p38 MAPK in regulating nSMase2 translocation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, PKC- δ has been implicated in regulation of apoptosis of U937 cells (Jang et al, 2003), whereas PKC-ε is involved in UV-induced carcinoma development (Aziz et al, 2007). A role for PKCs in p38 MAPK activation has also been suggested in response to TNF and hyperglycemia (Woo et al, 2005; Nomiyama et al, 2007), and PMA induces p38 MAPK activation in many cell types, including MCF-7, A549, and A172 glioblastoma cells (Chang et al, 2005; Kitatani et al, 2006; Nomura et al, 2007). Thus, some of the downstream effects of PKC can be attributed to its subsequent activation of p38 MAPK.…”
mentioning
confidence: 98%
“…In addition, in vitro studies showed that high concentration of glucose (which can result from sucrose feeding) induced pancreatic stellate cell (PSC) proliferation, resulting in increased extracellular matrix production and a consequent aggravation of fibrosis (37,38). High glucose and high insulin have been reported to have an additive effect on the activation and proliferation of rat PSCs (39).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that hyperglycemia promotes proliferation and activation of PSCs and stimulates collagen production of PSCs via protein kina-seC-p38 mitogen-activated protein kinase pathway, resulting in pancreatic fibrosis [59] .…”
Section: Clinical Studiesmentioning
confidence: 99%